2022
DOI: 10.55563/clinexprheumatol/ohsmuj
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of peripheral blood B cell subsets in Chinese patients with adult idiopathic inflammatory myopathies

Abstract: ObjectiveAbnormalities and hyperactivation of B cells have been described in idiopathic inflammatory myopathies (IIM). However, little is known about changes in the homeostasis of peripheral blood B cells in adult IIM patients. The aim of this study was to identify phenotypic alterations of B cell subsets and their relation to the overall clinical profile. Methods Blood samples were collected from 25 adult IIM patients and 15 healthy controls. Peripheral B cell subsets were classified into non-switched memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Cluster 3 composed of memory B cells, translational memory B cells, and plasmablast, suggests that increased frequency of memory B cells and plasmablast are associated with patients with anti-MDA5 antibodies. This is consistent with previous studies of abnormalities in B cell subset distribution in patients with IIM [14,25,35]. The results suggest that B cell subsets in IIM are heterogeneous.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cluster 3 composed of memory B cells, translational memory B cells, and plasmablast, suggests that increased frequency of memory B cells and plasmablast are associated with patients with anti-MDA5 antibodies. This is consistent with previous studies of abnormalities in B cell subset distribution in patients with IIM [14,25,35]. The results suggest that B cell subsets in IIM are heterogeneous.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, Jennifer et al [23] explored the function of Jo-1-binding B cells in patients with anti-synthetase syndrome (ASS) by recruiting 110 patients; Jose ne et al [24] analyzed the role of B cell subsets in the pathogenesis of DM by analyzing skeletal muscle biopsies from 23 IIM patients. Furthermore, Wang et al [25] found that dysregulation of B cell subsets was associated with the presence of rash, anti-MDA5 autoantibodies, and treatment e cacy in a cohort of 25 IIM patients.…”
Section: Introductionmentioning
confidence: 99%
“… 88 CD19 + B cell counts are higher in MDA5 + DM patients than in ARS + IIM patients. 102 Additionally, serum (ESR) levels are higher in the non‐survival group than in the survival group among MDA5 + DM patients, indicating that increased ESR may predict poor prognosis in MDA5 + DM patients. 103 …”
Section: Blood‐based Molecular Biomarkers In Mda5 ...mentioning
confidence: 98%
“…A high monocyte–lymphocyte ratio (MLR) (MLR >0.604) is an independent predictor of mortality in MDA5 + DM‐ILD patients, suggesting that MLR may predict poor prognosis in MDA5 + DM‐ILD patients 88 . CD19 + B cell counts are higher in MDA5 + DM patients than in ARS + IIM patients 102 . Additionally, serum (ESR) levels are higher in the non‐survival group than in the survival group among MDA5 + DM patients, indicating that increased ESR may predict poor prognosis in MDA5 + DM patients 103 …”
Section: Blood‐based Molecular Biomarkers In Mda5+dm‐ildmentioning
confidence: 99%
“…On the other hand, the immune system's dysregulation is responsible for numerous pathological implications in IIM. In Chinese patients, CD19+ B cells and naïve B cells are expanded, but a small number of memory B cells is found (9). Furthermore, the different levels of the B cell subtypes were different in different clinical subgroups: patients with a rash had lower nonswitched memory B cells.…”
Section: Reviewmentioning
confidence: 99%